Beyond "Natural" and "Cultural" Heritage: Toward an Ontological Politics of Heritage in the Age of Anthropocene. (May 2015) - Harrison, Rodney
<x content-type="archive" xml:space="preserve">Abstract</x> The critique of the separation of natural and cultural heritage is now well established. Rather than repeat arguments against what many would now acknowledge as an artificial separation, this paper considers the implications of working within the expanded field that is created for heritage when the dissolution of the boundaries between natural and cultural heritage is taken as given. I argue that embracing this dissolution allows us to reorient and reconceptualize heritage. Heritage is understood here as a series of diplomatic properties that emerge in the dialogue of heterogeneous human and non-human actors who are engaged in practices of caring for and attending to the past in the present. As such, heritage functions toward assembling futures, and thus might be more productively connected with other pressing social, economic, political, and ecological issues of our time. Indeed, we need not look far to comprehend alternative forms of heritage-making that already model such connectivity ontologies. Fundamental to understanding the value of these alternative heritage ontologies is the recognition of ontological plurality: that different forms of heritage practices enact different realities and hence work to assemble different futures. Following on from this point, I sketch out an ontological politics of and for heritage—a sense of how heritage could be oriented toward composing "common worlds" or "common futures, " while maintaining a sensitivity to the ways in which each domain of heritage relates to a particular mode of existence. At stake here is the acknowledgment that each such mode of existence produces its own particular worlds and its own specific futures. I do this within the context of a consideration of the implications of the recognition of a certain set of entanglements of culture with nature, the folding together of what we used to term the human and the non-human, which characterizes our contemporary moment. To illustrate these points, I introduce the framework for a new collaborative research program, Assembling Alternative Futures for Heritage, which considers the implications of working across an expanded field of heritage practices and attempts to reconfigure the relationship between heritage and other modalities of caring for the future.